Domestic violence against women in India and implementation of PWDV act, 2005 - Singh, Awadhesh Kumar; Singh, Amit (Madhav books, 2017)
Papers presented at National Seminar on "Domestic Violence Against Women and Implementation of Prevention of Women from Domestic Violence Act, 2005", organized by Gurukul Sewa Samiti from July 28-29, 2014 at Jaipur, India.